2012
DOI: 10.1164/rccm.201202-0368oc
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of the Constricted Human Airway by Tidal Expansion of Lung Parenchyma

Abstract: Rationale: In the normal lung, breathing and deep inspirations potently antagonize bronchoconstriction, but in the asthmatic lung this salutary effect is substantially attenuated or even reversed. To explain these findings, the prevailing hypothesis focuses on contracting airway smooth muscle and posits a nonlinear dynamic interaction between actomyosin binding and the tethering forces imposed by tidally expanding lung parenchyma. Objective: This hypothesis has never been tested directly in bronchial smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
87
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 72 publications
(84 reference statements)
14
87
1
Order By: Relevance
“…An attractive new preparation for studying reactivity of the small airway is the precision-cut lung slice (PCLS) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Clinical Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…An attractive new preparation for studying reactivity of the small airway is the precision-cut lung slice (PCLS) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Although there is no alveolar air-liquid interface and lung recoil is therefore not faithfully maintained, the muscle microenvironment roughly approximates in situ conditions (15). Additional practical advantages of the PCLS include ease of preparation, widespread applicability to nearly every animal species including human (22,25), and suitability for high-resolution imaging (19,21). In the PCLS, even responses to neural stimulation (20,23) and stretch (18,22,24) have been evaluated.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible that increased parenchymal inflammation, rather than airway inflammation, contributes to a reduced bronchodilatory response to DI in subjects with asthma by increasing parenchymal hysteresis. 38 Our laboratory 21,39 and others 40 have previously shown that ASM strain is the critical determinant of bronchodilation to DI. By use of fixed P tm DI, the stiffness of the airway wall determines the magnitude of ASM strain.…”
Section: Discussionmentioning
confidence: 95%
“…Mechanical stress can also alter ASM contractility (Fredberg et al 1997, Lavoie et al 2012, Noble et al 2013, Pascoe et al 2013. For example, the change in length that ASM undergoes during breathing maneuvers, such as during a deep inspiration, decreases the contractile capacity of ASM.…”
Section: Asm Plasticitymentioning
confidence: 99%